Catalytic Spectrophotometric Determination of Trace Amounts of Ag(I) using the Oxidation of 1,8-Dihydroxy-2-(4-sulfophenylazo)naphthalene-3,6- disulfonic Acid Trisodium Salt with Peroxodisulfate - KEYVANFARD, M.; POURETEDAL, H.R. (Asian Journal of Chemistry, 2010)
A simple and sensitive kinetic spectrophotometric method for determination of ultra trace amounts of silver(I) has been proposed. It is based on the oxidation of 1,8-dihydroxy-2-(4-sulfophenylazo)naphthalene-3,6-disulfonic acid trisodium salt (SPADNS) by peroxidisulfate in acetate buffered solution at pH 3.5 and in the presence of 1,10-phenanthroline as an activator at 35ºC. The reaction was monitored spectrophotometrically by measuring the decrease in absorbance of SPADNS at 510 nm in time period of 0.5-5.5 min from initiation of the reaction. The method allows the determination of silver concentration in the range 2.0-100.0 ng/mL, with the detection limit of 0.26 ng/mL. The relative standard deviation for ten replicate determinations of 0.040 and 0.10 μg/mL Ag(I) is 1.9 and 2.3%, respectively. The method has been applied to determination of silver in photographic solution and water.